THE IMPACT OF THE SPA BUSINESS MODEL ON UNIQLO'S FINANCIAL PERFORMANCE AND GLOBAL COMPETITIVENESS - Ayu Widia; Ayuningtyas Y Hapsari (LPPM STIE Muhammadiah Bandung, 2025)
The global fast fashion industry has witnessed tremendous growth in recent years, driven by consumer demand for affordable, trendy, and widely available clothing. This study investigates how key operational factors—Operating Profit, Store Expansion, and Inventory Turnover—affect Uniqlo’s financial performance and global market competitiveness. Using a quantitative explanatory approach, we analyzed secondary data from Fast Retailing’s quarterly financial reports spanning 2014 to 2023. Statistical analysis was conducted through multiple linear regression to identify the strength and direction of relationships among variables. The results reveal that Operating Profit has a significant positive impact on both Revenue Growth and Profitability, suggesting that operational efficiency is a major driver of sustainable growth. Store Expansion shows a direct and strong effect on Market Share, reinforcing the importance of global physical presence in the retail industry. Additionally, Inventory Turnover plays a vital role in enhancing both financial outcomes and operational responsiveness, positively influencing Revenue Growth, Market Share, and Profit Margins. This research contributes to a deeper understanding of how the SPA (Specialty Store Retailer of Private Label Apparel) business model supports Uniqlo’s competitive positioning. The findings offer practical insights for fashion industry stakeholders seeking to improve business performance through strategic operational decisions.